Unclaimed experience : trauma, narrative, and history - Caruth, Cathy (The Johns Hopkins University Press, 1996)
In Unclaimed Experience, Cathy Caruth proposes that in the widespread and bewildering experience of trauma in our century―both in its occurrence and in our attempt to understand it―we can recognize the possibility of a history no longer based on simple models of straightforward experience and reference. Through the notion of trauma, she contends, we come to a new understanding that permits history to arise where immediate understanding may not.